Quantitative polymerase chain reaction. - Peirson, S; Butler, J (2007)
Quantitative PCR (qPCR) has entered widespread use with the increasing availability of real-time PCR. By the incorporation of fluorescent dyes in the reaction mixture, increases in amplification products can be monitored throughout the reaction, enabling measurements to be taken in the exponential phase of the reaction, before the reaction plateau. Whatever the platform or chemistry involved, the starting point of a real-time assay is a tissue-specific RNA and the end point of a real-time reaction is an amplification plot. As such, rather than focusing on specific platforms or chemistries, herein we address the basic principles that underlie sample preparation, experimental design, use of internal controls, assay considerations, and approaches to data analysis. The advent of real-time PCR has enabled high-throughput analysis of multiple transcripts from small tissue samples, with an unparalleled dynamic range and sensitivity. However, to new users, this technique may seem to require extensive optimization and troubleshooting to obtain reliable data; this is further compounded by the mass of technical variations present throughout the literature. The aim of this article is to provide the necessary basics to get a quantitative real-time PCR assay up and running, and to address some of the problems that may arise and how these may be resolved.